Ionic liquids: physico-chemical, solvent properties and their applications in chemical processes - Singh, Geetanjali; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2008)
A new class of compounds, called as ionic liquids, has recently emerged as potential substitute for volatile organic solvents. Ionic liquids possess certain special physico-chemical characteristics that render them very useful in different areas of research and development. In this review, the physico-chemical properties and the applications of ionic liquids in chemical processes are critically discussed and recommendations made for probing further the poorly understood aspect of this newly emerging class of compounds.